Economic web-building behavior and behavioral investment trade-offs in a cobweb spider - Zhang, Haixin; Wen, Lelei; Li, Zichang; Li, Changchun (Frontiers in Ecology and Evolution, 2023)
Web-building spiders that build detritus-based bell-shaped cobwebs are model organisms for studies on behavioral plasticity because their web architecture components are easily quantified and defense and foraging investments are clearly separated.We investigated the web architectures and behavioral investments of the webs built by Campanicola campanulata under different weight (heavy, medium and light) detritus to research its cobweb architecture variation and analyzed the investment trade-off between foraging and defense.The results showed that spiders could actively choose lighter detritus to build webs to reduce material and energy cost. There was a clear trade-off between defense and foraging investment of spiders choosing different weight detritus for their webs. The total length of gumfooted lines (foraging investment) were longer for the spiders that chose lighter detritus, but the energy expenditure during web-building (defense investment) was higher for the spiders that chose heavier detritus.